Linked sediment and water‐column methanotrophy at a man‐made gas blowout in the North Sea: Implications for methane budgeting in seasonally stratified shallow seas. (7th November 2016) - Steinle, Lea; Schmidt, Mark; Bryant, Lee; Haeckel, Matthias; Linke, Peter; Sommer, Stefan; Zopfi, Jakob; Lehmann, Moritz F.; Treude, Tina; Niemannn, Helge
Abstract: Large quantities of the greenhouse gas methane (CH4 ) are stored in the seafloor. The flux of CH4 from the sediments into the water column and finally to the atmosphere is mitigated by a series of microbial methanotrophic filter systems of unknown efficiency at highly active CH4 ‐release sites in shallow marine settings. Here, we studied CH4 ‐oxidation and the methanotrophic community at a high‐CH4 ‐flux site in the northern North Sea (well 22/4b), where CH4 is continuously released since a blowout in 1990. Vigorous bubble emanation from the seafloor and strongly elevated CH4 concentrations in the water column (up to 42 µM) indicated that a substantial fraction of CH4 bypassed the highly active (up to ∼2920 nmol cm −3 d −1 ) zone of anaerobic CH4 ‐oxidation in sediments. In the water column, we measured rates of aerobic CH4 ‐oxidation (up to 498 nM d −1 ) that were among the highest ever measured in a marine environment and, under stratified conditions, have the potential to remove a significant part of the uprising CH4 prior to evasion to the atmosphere. An unusual dominance of the water‐column methanotrophs by Type II methane‐oxidizing bacteria (MOB) is partially supported by recruitment of sedimentary MOB, which are entrained together with sediment particles in the CH4 bubble plume. Our study thus provides evidence that bubble emission can be an important vector for the transport of sediment‐borne microbial inocula, aiding in the rapid colonization of the water column by methanotrophic communities and promoting their persistence close to highly active CH4 point sources.